The Role of Employee Engagement in Increasing Millennial and Gen Z Employee Retention - Wibaselppa, Anggawidia; Santosa, Tomi Apra; Batjo, Siti Nurjana; Fauzi, Rizal Ula Ananta; Nugraha, Aat Ruchiat; Sinaga, Hommy Dorthy Ellyany; Wulandari, Andi Sri Rezky (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to examine the role of employee engagement in increasing employee retention of Millennials and Gen Z in modern organizations. The research background is based on the high challenges in retaining a young workforce that is dynamic and easily switchable. The research method uses a quantitative approach with a survey of 30 respondents of Millennial and Gen Z employees from various industry sectors. Data were analyzed using multiple linear regression to test the influence of the employee engagement dimension—including emotional engagement, cognitive commitment, and social attachment—on employee retention intention. The results showed that all dimensions of employee engagement had a positive and significant influence on employee retention, with emotional engagement as the most dominant factor (β = 0.68; p < 0.01). The practical implications of this study emphasize the importance of developing holistic engagement programs, such as personalization training and interactive internal communication platforms, to increase employee loyalty of Millennials and Gen Z. The theoretical contributions of the research include an in-depth understanding of engagement mechanisms in the demographic context of the younger generation and Human Resources policy recommendations to strengthen retention strategies in the digital age.